Computational Fluid Dynamics Analysis of Wing-Tip Modifications on Tapered Wings to Enhance Aerodynamic Performance of Unmanned Aerial Vehicles - Ahmad Hafid; Ahmad Atif Fikri (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Unmanned Aerial Vehicles (UAVs) are widely deployed in applications that require high aerodynamic efficiency, extended endurance, and precise control. The aerodynamic performance of UAVs is strongly influenced by wing design, particularly at the wingtips, where intense vortices can generate significant induced drag and promote early stall. This study employs a full-factorial design of experiments (DoE) combined with computational fluid dynamics (CFD) simulations using the k–ω SST turbulence model to investigate the effect of wing tip modifications on various angle of attack (AoA). The results indicate that the maximum lift coefficient occurs at an AoA of 10° for all wingtip configurations, with the rounded-edge wingtip achieving the highest value (Cl = 0.125). The drag coefficient increases gradually from AoA 0° to 10°, followed by a sharp rise up to 15°, indicating early stall. The highest lift-to-drag ratio is obtained at AoA = 5°, where the rounded-edge wingtip demonstrates superior aerodynamic efficiency (Cl/Cd = 20.4). Analysis of the pitching moment coefficient reveals a nose-down tendency at low to moderate AoA, transitioning to an aggressive nose-up behavior at higher angles of attack. Overall, the rounded-edge wingtip provides the most favorable aerodynamic performance for fixed-wing UAVs, offering improved efficiency and stable longitudinal characteristics within low to moderate AoA operating regimes.